Common diskcyclic vectors - Bamerni, Nareen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, we study the common diskcyclic vectors for a path of diskcyclic operators. In particular, if  is a path of diskcyclic operators, we show that under certain conditions the intersection of diskcyclic vectors for theses operators is a dense  set.